THE EFFECT OF LEADERSHIP, COMPENSATION, MOTIVATION, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE OF CV BINTANG JAYA GRAFIKA BOYOLALI - Muhamad Nafi' Asrori; Abdul Halik; Siti Mujanah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This research aims to determine the extent to which the variables of leadership, compensation, motivation, and work environment influence the performance of the employees at CV Bintang Jaya Graphics Boyolali, both collectively (simultaneously) and individually (partially). A quantitative research approach was used with a total population of 66 employees. The sampling technique applied was total or saturated sampling method. Data were collected through questionnaires. Data analysis involved multiple linear regression, F-test, t-test, and the coefficient of determination (R²). The research shows that compensation and motivation have a significant influence on employee performance. Meanwhile, leadership and work environment do not have a significant influence. Keywords:Management performance, leadership, compensation, motivation, and work environment